The Body of the Artisan: Art and Experience in the Scientific Revolution - Smith, Pamela H. (Chicago, IL University of Chicago Press, 2004)
Since the time of Aristotle, the making of knowledge and the making of objects have generally been considered separate enterprises. Yet during the late sixteenth and early seventeenth centuries, the two became linked through a "new" philosophy known as science. In The Body of the Artisan, Pamela H. Smith demonstrates how much early modern science owed to an unlikely source-artists and artisans.From goldsmiths to locksmiths and from carpenters to painters, artists and artisans were much sought after by the new scientists for their intimate, hands-on knowledge of natural materials and the ability to manipulate them. Drawing on a fascinating array of new evidence from northern Europe including artisans' objects and their writings, Smith shows how artisans saw all knowledge as rooted in matter and nature. With nearly two hundred images,The Body of the Artisanprovides astonishingly vivid examples of this Renaissance synergy among art, craft, and science, and recovers a forgotten episode of the Scientific Revolution-an episode that forever altered the way we see the natural world.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); Cultural history; Science; Corporeality